The Purpose of Marks Gospel An Early Christian Response to Roman Imperial Propaganda - Winn, Adam (Mohr Siebeck, 2008)
Die Absicht des Markusevangeliums. Eine frühchristliche Antwort auf römisch-kaiserzeitliche Propaganda.
PublicationDate: 20080827
Keywords: Purpose of Marks Gospel -- Christology of Marks Gospel -- Vespasian -- Roman Imperia -- Neues Testament -- Array